1919–1920 metų Lietuvos nepriklausomybės karo nominacijos ir pripažinimai | Names and Recognition of the Lithuanian War of Independence, 1919–1920 - Gediminas Vitkus (Acta Historica Universitatis Klaipedensis)
Correlates of War (COW), an ongoing project initiated in the United States to monitor all the wars around the globe, covers the Estonian and Latvian wars of independence, and the war between Poland and Russia, but does not represent the Lithuanian War of Independence in detail. It only includes one episode of the war, the Polish-Lithuanian war. The article points out that this is partly correlated with the lack of a single term for these events in Lithuania. The author assesses the names of the war or wars of independence circulating in Lithuania, asking to what extent their differences have had an impact on the external (non)recognition of the War of Independence. After reviewing the paradoxical situation with war names circulating in Lithuania, the essay concludes with a reflection on what caused the establishment of the plural name in Lithuania. Despite this, the author argues that, from the perspective of external recognition, a singular name would better represent the nature of the processes that occurred in 1919 and 1920, and would contribute more to the consolidation of the national identity.